KEEPING QUALITY OF POMEGRANATE FRUIT (CV. MAHDAWI) BY PACKING, WRAPPING WITH ALOE VERA AND PUTRESCINE DURING COLD STORAGE - ABBAS , AREEN M.; BAMARNY, SARFARAZ F. A. AL (Journal of Duhok University, 2023)
Agricultural Engineering Sciences, University of Duhok, in which local pomegranate fruits were obtained in one of the private orchards located in the village of Armasht (fifty-three kilometers from the city of Duhok). Dohuk Governorate, Kurdistan Region/Iraq, to study the effect of packing type (non-packing and packing) and dipped fruits for 7 min in different concentration of (0, 15, 30% AV gel, and 1.5 and 3 mM PUT) on fruit quality of pomegranate during (0, 2, 3 month) cold storage at 6+1℃ with 85-90% RH. The fruits packed in closed polyethylene bags were significantly superior to the non-packed fruits, in total soluble solids%, total acidity% and vitamin C, while they gave the lowest weight loss % during the cold storage period.  As for the effect of AVgel and PUT solution results explained that dipped fruit in 30% AV gel Significantly reduce the fruit weight loss% and caused increase total soluble solids%, vitamin C, and juice density, and total acidity % compared to the other value. When storage progressed, a significant decrease was observed in TSS, titratable acidity, vitamin C and juice density in juice of all treated and untreated pomegranate fruits. The interaction of packing, storage period and dip treatments had significantly a positive effect on the quality pomegranate fruits